Migraines - Stafford, Diane; Shoquist, Jennifer (--For dummies., 2026)
"Haven't you spent enough time juggling schedules and cancelling events when headache pain sidelined you? You can put those days behind you with up-to-date information on the when-why-how of migraines and a whole-of-body approach to micromanaging them. Migraines For Dummies supplies the answers you've been looking for in the form of straightforward explanations and reliable advice to help you tackle symptoms, avoid triggers, and find the best medical support. You'll explore new drug therapies, including prescription meds, over-the-counter drugs, nerve stimulators, and alternative remedies. Plus, learn how to reduce migraine frequency by tweaking diet, sleep, and exercise. Updated with the latest research, this Dummies guide shows you how to balance medical care and lifestyle adjustments to fix that aching head of yours and upgrade your quality of life once and for all. Millions suffer from migraines. That's why it's key to stay on top of developments in diagnosis and treatment. If you or someone you love wrestles with headaches on a regular basis, let Migraines For Dummies deliver topnotch ideas that will change your life forever." --